Harmoni sosial dalam masyarakat multikultural di Indonesia - Rahmadhani, Fadilah Eka (Maliki Interdisciplinary Journal, 2026)
Indonesia is a nation rich in ethnic, religious, racial, and cultural diversity. This diversity presents both opportunities and challenges in building sustainable social harmony. This study aims to examine the concept of social harmony in Indonesia's multicultural society by focusing on factors that promote harmony, the role of multicultural education, religious moderation, and local wisdom as social cohesion tools. A qualitative literature review method was employed using relevant academic sources. The findings reveal that social harmony does not emerge spontaneously but is the result of collective efforts through inclusive education, interfaith dialogue, tolerance-based values, and equitable public policy. Factors such as cosmopolitan religious awareness, inclusive theology, and gotong royong cultural practices have proven effective as conflict resolution instruments and harmony builders. The implications of this study emphasize the importance of multicultural education reform and strengthening religious moderation as key strategies for building social harmony amid Indonesia's societal plurality.